The Intentional Selection Assumption - Colantonio, Joseph; Durkin, Kelley; Caglar, Leyla Roksan; Shafto, Patrick; Bonawitz, Elizabeth (Frontiers in Psychology, 2021)
There exists a rich literature describing how social context influences decision making. Here, we propose a novel framing of social influences, the Intentional Selection Assumption. This framework proposes that when a person is presented with a set of options by another social agent, people may treat the set of options as intentionally selected, reflecting the chooser’s inferences about the presenter and the presenter’s goals. To describe our proposal, we draw analogies to the literature in cognition on sampling inferences within concept learning. This is done to highlight how the Intentional Selection Assumption accounts for both normative (e.g., comparing perceived utilities) and subjective (e.g., consideration of context relevance) principles in decision making, while also highlighting how analogous findings in the concept learning literature can aid in bridging these principles by drawing attention to the importance of potential sampling assumptions within decision making paradigms. We present two behavioral experiments that provide support to this proposal and find that social-contextual cues influence choice behavior in respect to induced sampling assumptions. We then discuss the theoretical framework of the Intentional Selection Assumption alongside potential relationships it may have to contemporary models of choice. Overall, our results emphasize decision makers’ flexibility in respect to social-contextual factors without sacrificing systematicity regarding preference for specific options of higher value or utility.